How do Spanish consumers perceive different lettuce cultivation systems? Insights from explicit and implicit methods - Juan Diego Torres; Sara R. Jaeger; Patricia Puerta; Amparo Tárrega (Applied Food Research)
This study explores consumer perceptions of different agricultural systems to understand why some are regarded more favourably than others are. Five agricultural systems were compared in the context of lettuce cultivation: vertical indoor agriculture, small-scale local agriculture (local/small), high-tech greenhouses, urban community gardens, and industrial agriculture. Given the lack of knowledge among consumers about agricultural production, images and brief descriptions of the different systems were used as research stimuli. Explicit and implicit responses (as determined by eye tracking and facial coding) were recorded from 105 Spanish consumers. Local/small agriculture was the most favourably regarded of all aspects under consideration. Urban community gardens were the second most positively evaluated of the five agricultural systems; however, lettuce produced in this system was perceived as less safe to eat. Conversely, lettuce cultivated in high-tech greenhouses is regarded as safer to consume, yet this method of agriculture is also perceived as less sustainable. The emotional response was characterised by low intensity, with a notable exception in the case of vertical indoor farming, which elicited a stronger surprise reaction due to the limited familiarity of consumers with this farming system. Further research should include additional perceptions, such as naturalness and freshness, and analyse individual consumer responses to identify further differences among agricultural systems.